Online learning applied to a course on rational therapeutics: an international comparison between final year students of two medical schools. (10th January 2013) - Likic, Robert; White, Casey; Cinti, Sandro; Purkiss, Joel; Fantone, Joseph; Chapman, Chris; Bielen, Luka; Francetic, Igor; Engleberg, Cary
<x xml:space="preserve">Abstract</x> Introduction Poor prescribing is probably the most common cause of preventable medication errors and many of these events involve junior doctors. In 2009, an electronic problem‐based therapeutics course developed at the University of Michigan Medical School (UMMS) was translated and adapted for use at the University of Zagreb Medical School (UZMS). Methods After students from both schools took the course in 2010, we compared their responses with an online questionnaire addressing the course quality and its effectiveness. Results There were no statistically significant differences in the overall average grades awarded for the course (UZMS 4.11 ± 0.86 vs. UMMS 3.96 ± 0.93; 95% CI mean difference (MD) – 0.36, 0.07; P = 0.175) with both student groups expressing high satisfaction rates with its quality, accessibility and overall design. UZMS students reported spending less time working through the course than their American colleagues (2.14 ± 1.01 vs. 2.89 ± 1.02 on a five point Likert scale; 95% CI MD 0.51, 0.99; P < 0.05). Furthermore, Croatian students indicated greater difficulty with course materials (3.54 ± 0.59 vs. 3.25 ± 0.59; 95% CI MD – 0.42, – 0.15; P < 0, 05) and weekly multiple choice questions (3.83 ± 0.62 vs. 3.4 ± 0.61; 95% CI MD – 0.58, – 0.29; P < 0, 05) compared with the UMMS students. Conclusion It is possible to adapt and translate successfully whole online teaching resources and implement them internationally in different countries and health care systems, achieving similar, high student satisfaction rates while decreasing administrative and cost burdens. Web based learning may have great potential to offer a cost effective and safe environment in which prescribing skills can be improved.